TLR9- and CD40-Targeting Vaccination Promotes Human B Cell Maturation and IgG Induction via pDC-Dependent Mechanisms in Humanized Mice - Cheng, Liang; Li, Guangming; Pellegry, Caroline Marnata; Yasui, Fumihiko; Li, Feng; Zurawski, Sandra M.; Zurawski, Gerard; Levy, Yves; Ting, Jenny P.-Y.; Su, Lishan (Frontiers in Immunology, 2021)
Mice reconstituted with a human immune system (humanized mice) provide a robust model to study human immunology, vaccinology, and human infectious diseases. However, the development and function of B cells in humanized mice is impaired. B cells from humanized mice are immature and are impaired in IgM to IgG isotype switch in response to infection or vaccination. In the present study we report that Toll-like receptor 9 (TLR9) agonist CpG-B combined with CD40-targeting vaccination triggered human B cell immunoglobin class-switch from IgM+ to IgG+ B cells in humanized mice. Human B cells from mice vaccinated with CpG-B as adjuvant were more mature in phenotype and produced significant levels of both total IgG and antigen-specific IgG. We found that CpG-B treatment activated human pDCs (plasmacytoid dendritic cells) in vivo to induce interferon-alpha (IFN-α)expression in humanized mice. Pre-depletion of human pDC in vivo abrogated the adjuvant effect of CpG-B. Our results indicate that TLR9 and CD40-targeting vaccination triggers human B cell maturation and immunoglobulin class-switch in a pDC-dependent manner in humanized mice. The findings also shed light on induction of human IgG antibodies in humanized mouse models.